Et Per Højholt-brev om »Havet komplet« - Jørgensen, Aage (Danske Studier, 2025)
‘Havet komplet’ appeared in Per Højholt’s Lynmuseet og andre blindgyder (1982; The Lightning Museum and other Blind Alleys). The author commented on it in a letter from 1991 addressed to Aage Jørgensen. This letter is a source for understanding Højholt’s po-etics. The letter is published and annotated in this article.